Epidemiology of cardiovascular risk factors in two population-based studies. (September 2018) - Olmastroni, Elena; Shlyakhto, Evgeny V.; Konradi, Aleksandra O.; Rotar, Oxana P.; Alieva, Asiiat S.; Boyarinova, Maria A.; Baragetti, Andrea; Grigore, Liliana; Pellegatta, Fabio; Tragni, Elena; Catapano, Alberico L.; Casula, Manuela
Abstract: We aimed to compare cardiovascular risk factors prevalence in Italy and Russia through cross-sectional database analysis. The study has been based on data from ESSE-RF and from baseline of PLIC study, two population-based epidemiological studies aimed to investigate prevalence of risk factors and evaluating contribution of traditional and new risk factors into morbidity and cardiovascular mortality. A total of 2203 patients with left and right intima-media thickness (IMT) measurements constituted the source population (1205 from PLIC study and 998 from ESSE-RF study). Sample of ESSE-RF study had slightly more diabetic and hypertensive individuals, while the percentage of subjects with high cholesterol value was lower than in the other sample (67.1% vs 79.9%). The median LDL-C value was higher among individuals not treated with statins in the PLIC sample (p < 0.001), while was comparable among subjects receiving statin therapy. On the other hand, the percentage of individuals with positive cardiovascular history was higher in ESSE-RF sample. This could also explain the higher mean IMT value (0.71 ± 0.17 vs 0.63 ± 0.13) in the whole sample, and among patients without past cardiovascular events (regardless of statin treatment), despite some differences in major risk factors. Despite Russian and Italian populations are culturally and geographically different, they are not so different based on characteristics analyzed.